ANALISIS YURIDIS WANPRESTASI DALAM KONTRAK SUBKONTRAKTOR: STUDI PUTUSAN MAHKAMAH AGUNG NOMOR 1796 K/PDT/2015 T - debora, caroline (SIGHAT: JURNAL HUKUM EKONOMI SYARIAH, 2025)
This research analyzes the legal aspects of default in subcontractor contracts through an examination of Supreme Court Decision Number 1796 K/Pdt/2015 involving a dispute between PT Teduh Karya Utama as subcontractor and PT Boma Bisma Indra (Persero) as main contractor in a palm oil factory construction project. The research method employed is normative juridical with qualitative-prescriptive analysis of judicial considerations and the application of contract law norms. Research findings indicate that the Supreme Court rejected the subcontractor's claim due to inability to prove work completion according to contract specifications, while evidence demonstrated that the main contractor completed the work with the subcontractor's knowledge. This decision applies the principle of exceptio non adimpleti contractus, affirming that a party failing to fulfill its obligations cannot demand the other party to fulfill payment obligations. The research concludes that determining default in construction contracts requires comprehensive evidence of performance fulfillment from aspects of physical progress, work quality, and compliance with contractual specifications, as well as the importance of systematic documentationas evidence in dispute resolution. The legal implications of this decision provide legal certainty regarding standards of proof and the responsibilities of parties in construction subcontractor contracts in Indonesia.